The learning environment at a public university in northern Chile: how is dental education perceived by students? - José Pablo Tisi-Lanchares; Luis Barrios-Piñeros; Ismael Henríquez-Gutiérrez; Gerardo Durán-Ojeda (Universidad de Antioquia, 2017)
Introduction: the learning environment is considered essential in health sciences careers due to its significant influence on students overall learning achievements. The DREEM questionnaire was developed as a tool to obtain this environment's profile. In Chile, the learning environment has been studied in medical schools but no information is available on the field of public dentistry schools. The goal was to determine the students' perception of the learning environment in the dental career at Arturo Prat University in Iquique (Chile), based on the DREEM questionnaire. Methods: the Spanish version of DREEM was applied to 103 volunteers. Students were grouped in three levels: basic (first year), pre-clinical (second and third years) and clinical (fourth and fifth years). Data were processed and scores were determined for each level and for each DREEM domain (learning, teacher, academic perception, atmosphere, and social perception) which constitutes the learning environment. The Tukey test was used to determine statistical differences between groups. Results: no significant differences were found between the basic and the pre-clinical levels, but statistical differences were found at the clinical level. The overall score was 117.81/200, meaning a "more positive than negative" environment, despite a decrease in perception from the basic to the clinical level. Conclusion: the learning environment is perceived positively by students, despite a decreasing perception from the basic to the clinical level, mostly due to psychosocial factors.